Bio-Based Self-Healing Mortar - Md Yunus, Balqis (International Journal of Integrated Engineering, 2019)
This paper investigates the effects of alkaliphilic spore-forming bacteria of the genus Bacillus on the compressive strength of the mortar cube and the healing capacity of the bacteria as healing agent on mortar containing crack. The experiments were carried out using cube test, stereomicroscopy and environmental scanning electron microscopy (ESEM). Cracked mortar specimen with and without the presence of the bacteria-healing agent were prepared. Results showed that the inclusion of these bio-healing agent in mortar mixtures cause more pore volume, which has no significant effect on compressive strength development at 28 days. In the series of healing capacity test, the cracks were significantly healed in bacteria-based than in control specimens after 28 days incubated in water bath and thus, increase permeability resistance of bacteria-based mortar specimens.